Design and Development of a Non-Invasive Breathing Monitoring System for Asthma Patients - Eabis, Tiba Sadeq Razzaq; Hamzi, Tuka Sajid Abass; Mohammed Ali , Soukina Salim; Masood, Huda Masood Khashin (Journal of Science in Medicine and Life, 2025)
Asthma is a chronic respiratory condition affecting millions worldwide, characterized by airway inflammation, bronchoconstriction, and variable airflow obstruction. Monitoring respiratory patterns in asthma patients is crucial for disease management, treatment optimization, and early intervention to prevent exacerbations. However, conventional spirometry and peak flow meters are often cumbersome, require active participation, and may not capture real-time data outside clinical settings. To address these challenges, we present a novel non-invasive breathing monitoring system tailored for asthma patients. Our system utilizes a wearable sensor device equipped with advanced signal processing algorithms to continuously monitor respiratory parameters in real-time. The device employs non-contact sensing technology, eliminating the need for direct skin contact or respiratory accessories, thereby ensuring patient comfort and compliance. The core components of the system include a respiratory sensor, microcontroller unit, wireless communication module, and a user-friendly interface for data visualization and analysis. The respiratory sensor employs radar-based technology to detect subtle chest movements associated with breathing, enabling accurate and reliable monitoring of respiratory rate, tidal volume, and breathing patterns. The microcontroller unit processes the raw sensor data in real-time, applying advanced signal processing techniques to extract relevant respiratory parameters. The wireless communication module enables seamless data transmission to a smartphone application or cloud-based platform for remote monitoring by healthcare providers and personalized asthma management. Preliminary evaluation of the system demonstrates promising results in terms of accuracy, reliability, and usability.